Monotheism and Christology in Greco-Roman Antiquity - Novenson, Matthew V. (Novum Testamentum, Supplements Ser, 2020)
Intro -- Contents -- Preface -- Abbreviations -- Translations -- Notes on Contributors -- Chapter 1 Introduction -- Chapter 2 The New religionsgeschichtliche Schule at Thirty: Observations by a Participant -- Chapter 3 The Universal Polytheism and the Case of the Jews -- Chapter 4 The Divine Name as a Characteristic of Divine Identity in Second-Temple Judaism and Early Christianity -- Chapter 5 Jesus' Unique Relationship with YHWH in Biblical Exegesis: A Response to Recent Objections -- Chapter 6 God and Glory and Paul, Again: Divine Identity and Community Formation in the Early Jesus Movement -- Chapter 7 Confessing the Cosmic Christ (1 Corinthians 8:6 and Colossians 1:15-20) -- Chapter 8 One God, One Lord in the Epistle of James -- Chapter 9 Between Jewish Monotheism and Proto-Trinitarian Relations: The Making and Character of Johannine Christology -- Chapter 10 God and Christ in the Earlier Martyr Acts -- Chapter 11 Gnosis and the Tragedies of Wisdom: Sophia's Story -- Chapter 12 The One God Is No Simple Matter -- Chapter 13 How High Can Early High Christology Be? -- Index of Ancient Sources -- Index of Modern Authors -- Index of Subjects.